Caracterización del paisaje y análisis del límite oeste del Parque Nacional Carara, Costa Rica: implicaciones para la conservación de la biodiversidad - Quesada-Acuña, Sergio Gabriel (2012)
It is unknown if the current size and shape of protected areas (PA) in Costa Rica favors retention of viable populations of wildlife. The western border of Carara National Park (CNP) and its surroundings were characterized at a landscape level in order to consider their implications for biodiversity conservation. 54 400 hectares of Costa Rican Central Paciic tree cover were analyzed (1997, 2000, 2005) to calculate the size of the PAs, mean shape index, mean patch fractal dimension and edge density. Aside from that, we performed eight habitat evaluations on the western border of the CNP (“costanera-sur” highway) to assess tree composition, regeneration, litter, horizontal obstruction, and canopy cover. It was determined that the PAs were between 36 and 5 242 hectares long. We observed that the tree cover increased from 21 231,8 hectares in 1997 to 29 006,9 hectares in 2000, and decreased to 26 933,4 hectares in 2005. We found out that most of the tree cover (2005) belongs to CNP and ZP Cerros de Turrubares, but both of them present high values of edge density and mean shape index, suggesting that they are susceptible to alteration and fragmentation. The four evaluated points have a similar successional stage. In order to maintain the potential of CNP as an area for biodiversity conservation, we recommend reducing the maximum speed limit in the region adjacent to the park. It is also important to establish frequent monitoring of the tree cover and promote reforestation programs to create corridors that stop the area’s fragmentation and facilitate biodiversity conservation.